2014
DOI: 10.1039/c4ra00274a
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic manipulation of a filamentous fungus by the proteasome-inhibitor bortezomib induces the production of an additional secondary metabolite

Abstract: The use of epigenetic modifiers, such as histone deacetylase inhibitors and DNA methyltransferase inhibitors, has been explored increasingly as a technique to induce the production of additional microbial secondary metabolites. The application of such molecules to microbial cultures has been shown to upregulate otherwise suppressed genes, and in several cases has led to the production of new molecular structures. In this study, the proteasome inhibitor bortezomib was used to induce the production of an additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
(44 reference statements)
0
25
0
Order By: Relevance
“…The other NOE correlations were almost identical with those of the A form, suggesting the same relative configurations. The 1 H-NMR integral area showed that the two distinct sets of signals can be observed in an approximately 3:5 (A:B, Figure S21) ratio in DMSO-d 6 . On standing in MeOD-d 4 , the equilibration changed to be 1:4 (A:B, Figure S27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other NOE correlations were almost identical with those of the A form, suggesting the same relative configurations. The 1 H-NMR integral area showed that the two distinct sets of signals can be observed in an approximately 3:5 (A:B, Figure S21) ratio in DMSO-d 6 . On standing in MeOD-d 4 , the equilibration changed to be 1:4 (A:B, Figure S27).…”
Section: Resultsmentioning
confidence: 99%
“…Thus 2 and 3 might be artificial products. 4 was found to be a mixture of two equilibrium structures in solution formed by the same acetalization reaction, the 1 H-NMR integral area showed the two distinct sets of signals can be observed in an approximately 3:5 (A:B) ratio in DMSO-d 6 and 1:4 in MeOD-d 4 . 1 contains minor impurities too.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oberlies and coworkers took a slightly different approach to this method, using the proteasome inhibitor bortezomib to induce a filamentous fungus to produce cryptic metabolite 11 (Fig. 1) (VanderMolen et al 2014). While mode-of-action restrictions largely limit this method's application to fungi, the McArthur group was able to apply it in Streptomyces coelicolor (Moore et al 2012).…”
Section: Applicationsmentioning
confidence: 99%
“…Thus, DNMT and HDAC inhibitors serve as effective elicitors of fungal secondary metabolite. The use of proteasome inhibitors takes advantage of the same underlying mechanism in an indirect manner: proteasomes degrade many proteins, including several transcriptional regulators (VanderMolen et al 2014).…”
Section: Mechanismmentioning
confidence: 99%